OP0070 THE RISK OF PRECANCEROUS LESIONS OF THE BREAST AND CERVIX UTERI IN PATIENTS WITH AUTOIMMUNE RHEUMATIC DISEASES: A NATIONWIDE POPULATION STUDY IN TAIWAN. (2nd June 2020) - Tsai, P. H.; Kuo, C. F.
Abstract : Background: Precancerous lesions are pathologically atypical tissues which share part of abnormal features of cancerous tissue under microscopic examination but lack the ability of uninhibited growth and distant metastasis. Some of the measures to screen for precancerous tissues have gained popularity because supporting evidence indicates the beneficial effects on cancer incidence and mortality [1, 2]. However, the roles of these screenings and the risk of precancerous lesions in patients with autoimmune diseases have not been clarified. We aim to exam the risk of precancerous lesions among different autoimmune diseases. Objectives: To determine whether the Taiwanese autoimmune rheumatic diseases (ARDs) patients have a higher risk of precancerous lesions of the breast and cervix uteri. Methods: The Taiwan national breast cancer screening program provides biennially mammography for women above 45 years old or with a positive family history of breast cancer above 40 years old. The national cervical cancer screening program provides Pap smear test once every three years for women age above 30 years old. Using the National Health Insurance (NHI) database, we identified a cohort of 6 different groups of ARDs patients in Taiwan between 2004 and 2014. We linked the data from the national screening program of breast and cervical cancer and the NHI database to estimate the standardized incidence ratios (SIRs) of precancerous lesions (atypical lobular and ductal hyperplasia of the breast, carcinoma in situ of the breast, cervical intraepithelial neoplasia 1 to 3 of cervix uteri and carcinoma in situ of cervix uteri) in patients with ARDs compared with the general population. Results: From 2004-2014, we identified 64, 904 patients with autoimmune diseases. Table 1 shows the number of patients receiving the screening programs. The standardized incidence ratio (SIR) of precancerous lesion of the breast was elevated in patients with rheumatoid arthritis (SIR, 2.21; 95% CI, 1.21-3.46) and Sjögren syndrome (SIR, 5.77; 95% CI, 2.63-9.85). The incidence of precancerous lesion of cervix uteri was elevated in patients with surveyed ARDs compared with the normal population, particularly for patients with systemic lupus erythematosus (SIR 28.94; 95% CI, 24.52-33.70) and inflammatory bowel disease (SIR, 27.50; 95% CI, 7.40-56.32) (Table 2 ). Conclusion: Precancerous lesions in the breast and cervix uteri were higher in female patients with ARDs and they should receive stringent screening program. References: [1]Tabar L, et al. Beyond randomized controlled trials: organized mammographic screening substantially reduces breast carcinoma mortality. Cancer 2001, 91(9):1724-1731. [2]Peirson L, et al. Screening for cervical cancer: a systematic review and meta-analysis. Syst Rev 2013, 2:35. Disclosure of Interests: None declared